Conservative treatment in early stage endometrial cancer: a review - Trojano, Giuseppe; Olivieri, Claudiana; Tinelli, Raffaele; Damiani, Gianluca Raffaello; Pellegrino, Antonio; Cicinelli, Ettore (Acta Biomedica Atenei Parmensis, 2019)
Endometrial Cancer (EC) is the commonest gynecological cancer and its incidence is increasing. The diagnosis of endometrial carcinoma in young women of childbearing age is rare. Indeed, only 4% of patients with endometrial carcinoma are <40 years of age. It’s typically diagnosed in postmenopausal women. The standard approach for the management of endometrial cancer in young women of childbearing age is hysterectomy and bilateral salpingo-oophorectomy with or without lymphadenectomy but is not ideal for women interested in future fertility. We reviewed the published literature to clarify in fertile women who have not yet fulfilled their desire for motherhood, what are the strategies, the risks of a conservative treatment of early stage of Endometrial Cancer and what are the obstetric outcomes in this patients. Recently, several studies have reported encouraging results on fertility-sparing management of EC with high dose of progestins in selected women associated or not with hysteroscopic resection.